Nongenomic actions of aldosterone and progesterone revisited - Wendler, Alexandra; Albrecht, Christian; Wehling, Martin (Steroids, 2012)
After almost 30years of research, the existence of nongenomic steroid actions is no longer disputed. Yet, there is still a debate on the nature of receptors involved, and answers to the inherent questions are important for translational activities. In the case of aldosterone, the existence of receptors different from the classic mineralocorticoid receptors (MR) had been postulated 25years ago as the pharmacology of about 50% of rapid actions of aldosterone reported so far is incompatible with MR involvement (insensitivity to classic MR antagonists). Candidates proposed as alternatives to MR were protein kinase C, sodium-potassium ATPase or aberrant forms of MR, none of which supported convincing evidence to represent ‘the aldosterone membrane receptor’. Early in 2011, data on GPR30 showed its involvement in rapid aldosterone action, and major pharmacological aspects of this action are compatible with the landmark deviations from MR pharmacology mentioned above. GPR30, therefore, may be a receptor candidate for nongenomic aldosterone action. Similarly, a variety of promising candidates mediating rapid progesterone action has been described, including progesterone receptor membrane component 1 (PGRMC1) which seems to be associated with tumor proliferation, and membrane progesterone receptor (mPR) originally identified in fish with potential linkage to reproductive processes. So far, no candidate was unanimously convincing. In 2010, two independent groups reported that CatSper, a calcium channel, is a strong receptor candidate for the rapid action of progesterone on sperm fertilization. With these novel receptors cloned, translational activities ultimately leading to new drugs for cardiovascular protection (in the case of aldosterone) or fertilization benefits (for progesterone) are much more promising.